Mixed Weyl semimetals and low-dissipation magnetization control in insulators by spin–orbit torques - Jan-Philipp Hanke (Nature Portfolio, 2017)
Electric-field control of magnetization switching is highly promising for low-dissipation spintronics. Here, the authors propose an electrically induced topological phase transition mediated by spin orbit torques as attractive way to control magnetization in absence of longitudinal charge currents.